(untitled) (Bangladesh Journal of Otorhinolaryngology, 2021)
Purpose: To analyze and realize the importance of the Eustachian tube dysfunction (ETD) in the pathogenesis of the middle ear infections as to raise the awareness amongst the Otolaryngologists consider the tubal dysfunctions in the management of the otitis media. Materials and methods: 50 patients of aural discharge, aural fullness, aural pain, hearing loss and tinnitus along with nasal obstruction were selected from July 2013 upto December 2013 in the outpatient department (OPD) of Otorhinolaryngology - Head and Neck Surgery dept. of Dhaka Medical College Hospital under a specific prospective study protocol. All patients of aural fullness, hearing loss, aural pain, tinnitus, aural discharge along with nasal obstruction with or without sore throat were included; patients of sensorineural hearing loss, primary external ear pathology, ear malignancy and congenital ear diseaseswere excluded. Results: 58% patients were below 20 years, 50% were children, 64% were male and 36% female. 62% patients got aural fullness, 60% hearing loss 40% mild, 14% moderate, 6% severe conductive and 8% mixed), 26% tinnitus, 32% aural discharge and 30% aural pain and amongst the patients of otitis media with effusion (OME), 100% got hearing loss, 73% aural fullness, 33% tinnitus, 27% aural pain and 13% dizziness. 78% patients got septal deviation, 58% hypertrophied inferior turbinates (HIT), 32% enlarged adenoids (EA), 62% allergic rhinitis, 26% acute upper respiratory tract infection (URTI), 4% nasal polyps and 48% sinusitis/mucosal thickening and amongst the children, 64% got enlarged adenoids, 56% HIT, 76% septal deviation (SD), 24% acute URTI, 4% antrochoanal polyp, 20% adenoid with HIT and 44% adenoid with SD. Regarding findings in the patients of enlarged adenoid, 37.5% patients got eustachian tube dysfunction (ETD) and 62.5% got hearing loss due to OME as well as acute otitis media (AOM), chronic otitis media (COM) and it showed that mild adenoid caused ETD occasionally on URTI but mild adenoid with HIT caused OME. Conclusion: The obstructive nasal lesions are intermingled with otitis media, so this association should be sought out and underlying nasal lesions must be managed if any as a part of treatment of the otitis media. Bangladesh J Otorhinolaryngol 2021; 27(2): 159-169